Investigating the Eolian Context of the Last Glacial Maximum Occupation at Kawanishi‐C, Hokkaido, Japan. Issue 3 (1st April 2014) - Izuho, Masami; Hayashi, Kazuhiro; Nakazawa, Yuichi; Soda, Tsutomu; Oda, Noriyoshi; Yamahara, Toshiro; Kitazawa, Minoru; Buvit, Ian; Buvit, Ian; Carson, Mike T.
<x xml:space="preserve">Abstract</x> As debates about the late Pleistocene human occupation of northeast Asia continue, the Last Glacial Maximum (LGM) prehistory of Hokkaido becomes more relevant. A geoarchaeological evaluation of key sites on the island will provide important evidence to understand human adaptive responses to LGM environments. Kawanishi‐C is located on the middle terrace of the Satsunai River, eastern Hokkaido. Previous salvage excavations totaling 5756 m2 revealed three archaeological layers in eolian sediments: (1) an early Jomon component above the Ta‐d tephra (∼7000 cal. yr B.P.), (2) a microblade component between the Ta‐d and En‐a tephras (∼15, 000 cal. yr B.P.), and (3) a blade/flake‐based assemblage between the En‐a and Spfa‐1 tephras (27, 000–25, 000 cal. yr B.P.). Integration of geoarchaeological investigations and statistical analysis of the artifacts' spatial distribution indicates that the relatively low energy eolian matrix preserved the site's behavioral context, though some post‐depositional agent, such as frost heaving, may have slightly displaced the artifacts vertically.